Adolescents' Patterns of Citizenship Orientations and Correlated Contextual Variables: Results From a Two-Wave Study in Five European Countries. Issue 8 (November 2021) - Tzankova, Iana; Prati, Gabriele; Eckstein, Katharina; Noack, Peter; Amnå, Erik; Motti-Stefanidi, Frosso; Macek, Petr; Cicognani, Elvira
Studies on youth participation tend to characterize youth as either active and trustful or as passive and alienated. This cross-national and longitudinal study examines patterns of citizenship orientations characterized by both manifest and latent involvement differentiated by one's position toward institutional politics (trustful or distrustful) among 1, 914 adolescents from five European countries (53.5% female; Mage = 16.27). Demographic and proximal contextual correlates associated with different orientations at a 1-year interval were also assessed. Latent profile analysis identified four groups of citizenship orientations among adolescents: engaged trustful, engaged distrustful, unengaged trustful, and unengaged distrustful. Differences of membership likelihood were found for background characteristics (gender and family income), school characteristics (track, democratic climate, student participation, and its perceived quality), family, and peer norms of participation.